Design of an Android Based Garbage Transport (Angkut's) Application - Muhamad Alda; Tamaulina Barus; M. Farhan Alyuda; Novtra Refiardiansyah Nasution; Muhammad Ridho Nasution (Universitas Islam Kuantan Singingi, 2024)
The waste problem in urban areas, such as Belawan, Medan, is exacerbated by population growth and inadequate waste management systems, resulting in environmental degradation. To address this issue,